A transição agroecológica no assentamento rural Fazenda Pirituba: percepções, práticas e perspectivas - Narezi, Gabriela (Universidade Federal de São Carlos, 2008)
The importance of agroecologic transition for the agricultural nesting in the agrarian reform it s as an alternative front to the economic situation, in the recovery of degraded areas, the balance of agroecosystems and the viability of alimentary agricultural production to attend the needs of the families. The objective of this research was to analyze the agroecologic transition in the agricultural nesting Pirituba farm, in the cities of Itapeva and Itaberá, SP. The used methodology was the research-action and bibliographies. In the field work participative methodologies and half-structuralized interviews had been used. Five groups of agroecologic experimentation, the pointers of sustainability and the phases of each experimental agroecologic transition was identified and analyzed. It was shown that some families had interest in proceed in the agroecologic transition and that some areas demonstrated potential for agroecologic production. However, the continuity of these practices is compromised by some factors representing challenges for the families and also for the public policy of sustainable agricultural development. This work presents the perceptions, practice and perspective for the agroecologic transition in the agricultural nesting Pirituba Farm.
Agroecologic transition in the agricultural nesting Pirituba farm: perceptions, practice and perspective
Keywords: Agricultura; Agroecologia; Assentamentos rurais; Desenvolvimento rural; Políticas públicas; Sustentabilidade; Transição agroecológica; Agroecologic transition; Agricultural nesting; Agricultural development; Production diversity; Indicators of sustainability; CIENCIAS AGRARIAS